Changes of retinal ganglion cell–inner plexiform layer thickness and visual acuity in patients with diabetic macular edema treated with Aflibercept - Mouna M. Alsaad; Amin B. Shehadeh; Iyman M. Alsaad; Khalid A. Alubous; Jehad S. Meqbil; Mohammed Z. Qablawi; Saif Aldeen S. AIRyalat; Rawan A. Elubous (Delta Journal of Ophthalmology)
Background Anti-vascular endothelial growth factor agents have now become the first line of treatment for diabetic macular edema (DME). Changes in the thickness of the individual retinal layers including the ganglion cell–inner plexiform layer (GC–IPL) might serve as a biomarker for the response to treatment. Aim The aim of this study was to evaluate the effect of intravitreal injections of Aflibercept on the average thicknesses of the GC–IPL in naïve eyes and on the visual acuity in patients with DME. Patients and methods This is a retrospective observational study that included 224 naïve eyes of 224 patients having DME. It compared the changes in the GC–IPL thickness at baseline and after receiving three loading doses of Aflibercept followed by as needed protocol for 12 months. All patients had optical coherence tomography imaging at baseline (with GC–IPL thickness measurement) and at the 12-month visit. The change in GC–IPL thickness was measured and was correlated with best-corrected visual acuity. Results During the study duration, a median of five injections of Aflibercept were given. There was a statistically significant decrease in the posttreatment values of the GC–IPL thickness from 89±13 to 84±14.7 µm (P=0.029). Moreover, a statistically significant association was found between the thickness reduction of the GC–IPL in the central macular area and the best-corrected visual acuity (r=0.9, P=0.005, Pearson coefficient=0.26). Conclusion The results of this study suggest that the reduction in the GC–IPL thickness can be used as a prognostic tool for the response to Aflibercept as it was associated with improved visual acuity.